Induction of Helianthus annuus Leaves Extract to HeLa cell Apoptosis and Cell Cycle Arrest in S, G2-M and M5 Phase - Mutiah, Roihatul; Ulfah, Jauza; Amrulloh, Muhammad Firman; Suryadinata, Arief; Indrawijaya, Yen Yen Ari; Rahmawati, Ana (Indonesian Journal of Cancer Chemoprevention, 2022)
Helianthus annuus L. (H. annuus) is a potential medicinal plant for cancer therapy. The aims of this study is to identify profile the anticancer activity of H. annuus L. from its leaves, root, stem, and seed as well as to elucidate the apoptosis and cell cycle of the leaves. Ten-gram sample of the powder were extracted by using Ultrasound-Assisted Extraction (UAE) with 200 ml of 96% ethanol by comparison of 1:20 with three times replications. The determination of anticancer activity was used the MTT cell proliferation assay, while apoptosis test and cell cycle were applied with the flowcytometry test. The value of IC50 in 96% ethanol extract in the root and stem was >1,000 μg/mL; seed and leaves were 153.76 μg/mL; and 126.6 μg/mL, respectively. The apoptosis induction of H. annuus leaves extract treatment was 7.17% of apoptosis cells; 90.44% of necrosis, and 2.39% of living cells. The H. annuus leaves extract also significantly caused a decrease of cell percentage in G0-G1 phase (p<0.001) and an increase in G2-M phase (p<0.001). The H. annuus leaves extract had greater potential as anticancer instead of other parts. The adding of H. annuus leaves extract increased the HeLa cell apoptosis, decreased percentage of HeLa cells in G0-G1 phase, and increased percentage of HeLa cells in G2-M phase. Cell cycle mechanism test showed cell cycle arrest in S, G2-M, and M5 phase in 24 h, hence inhibited the mitosis process.Keywords: anticancer, Helianthus annuus L, apoptosis, cell cycle.